College and professional women`s basketball players` lower extremity injuries: a survey of career incidence - Gordon, A. I.; DiStefano, L. J.; Denegar, C. R.; Ragle, R. B.; Norman, J. R. (International Journal of Athletic Therapy & Training, 2014)
Context: Lower extremity injuries in women`s basketball players are generally presented as seasonal team incidence. Available data were reported by team athletic trainers to overseeing bodies yielding estimates of injury rates as a percentage of all injuries sustained. By summarizing career incidence of women`s basketball players` injuries, a new perspective indicating potential risk of injury can be considered. Objectives: To summarize the career incidence of lower extremity injuries in intercollegiate and professional women`s basketball players, examine the effect of anterior cruciate ligament (ACL) injury on professional basketball players` career longevity, and explore the relationship between ankle sprains and knee injuries in this population. Design: Survey. Participants: 246 elite-level women`s basketball players. Outcome Measures: Career incidence of lower extremity injury, professional career length, relationship between history of ankle sprain and ACL injury frequency calculations, and chi-square statistics. Results: Seventy-four of 85 (87.06%) professional Women`s National Basketball Association (WNBA) and 172/179 (96.09%) available collegiate Big East Conference (BEC) women`s basketball players completed the survey. Ankle sprains were the most frequently reported injury with 170/246 (69.11%) participants indicating at least one during their career. Patellar tendinopathy (28.46%), meniscal injury (22.76%), and ACL tear (21.54%) were also common. Professional career length in participants with an ACL reconstruction averaged 6.11 ± 3.20 seasons, more than the 5.70 ± 4.17 seasons reported by those without an ACL injury. Professional participants who did not report an ankle sprain were more likely to report an ACL tear (?2 = 10.96; p = .000932). Conclusion: Summarizing career incidence provides a new perspective of women`s basketball players` injuries. Ankle sprains and knee injuries were commonly reported, both more frequently than by traditional research methods. These data may assist in developing injury prevention and rehabilitation strategies for injured athletes. Key Words: women`s basketball, ACL injury, ankle sprain, basketball injuries